ELECTRON MICROSCOPIC EVIDENCE FOR PURIFICATION OF COCONUT ROOT (WILT) DISEASE PHYTOPLASMA - M. Mayilvaganan; J. J. Solomon (International Coconut Community, 2002)
Root (wilt) disease phytoplasma was purified from diseased coconut tissues using discontinuous Percoll gradient centrifugation method. Crude sap prepared from coconut was layered on a discontinuous Percoll gradient of 15, 30, 50 and 60%(v/v). After centrifugation at 20,000 g for 30 min, the turbid fraction formed on the top of 30% gradient in the diseased plant material was recovered, processed and fixed for electron microscopy. Electron microscopic examination of sections prepared from purified preparation of diseased plant material showed typical cells of root (wilt) phytoplasma with heterogeneous sizes and more or less spherical shape that are similar to those found in sieve elements of diseased tissues and salivary glands of infective (viruliforms) insect vectors. These purified phytoplasma bodies showed trilaminar membrane with internal materials of ribosome granules and DNA fibrils. However, the yield in terms of number of cells was fewer and in addition to intact bodies, free membranes and empty bodies lacking internal contents also were observed.